Potential anti-diabetic property of the aqueous extract of the leaves of Saba senegalensis Pichon (apocynaceae) in mice - Mamadou, Dosso; Adama, coulibaly; Ousmane, Coulibaly; Doudjo, Soro; J. David, N'guessan (International Journal of Pharmacology and Toxicology, 2020)
This study made it possible to demonstrate that Saba senegalensis has hypoglycemic and anti-hyperglyvemic effects in mice. The aqueous extract of Saba senegalensis from 75 to 250 mg / Kg bw causes a dose-dependent hypoglycemia ranging from 4.84 to 34.62% (p <0.01-0.05), in normoglycemic mice, 60 minutes after treatment. The Glucose-Induced Hyperglycemia Orally (OPGH) test showed that in the presence of Saba senegalensis aqueous extract at a concentration between 75 and 250mg/Kg bw, the glucose-induced hyperglycemic peak (3g/Kg bw) is reduced from 26.49 to 71.77% (p < 0.01-0.05), 30 minutes after treatment. Oral administration of the aqueous extract of this plant in doses up to 5000 mg / Kg bw resulted in no deaths in mice during two weeks of observation.Â Â Â